Greedy Algorithm to Support the Decision of Choosing the Fastest Aid Distribution Route After Flooding - Harahap, Sukma Ananda; Triase, Triase (Program Studi Sistem Informasi Fakultas Teknik dan Ilmu Komputer, 2024)
Flooding is one of the most common natural disasters in Indonesia, including in Merbau Sub-district, North Labuhan Batu Regency, North Sumatra. This disaster can cause huge losses, both material and non-material. One of the efforts to reduce the impact of flooding is to immediately distribute aid to affected communities. The distribution of post-flood aid requires careful planning so that it can run quickly and on target. In this research, we propose the use of greedy algorithm to support the decision of choosing post-flood aid distribution route in Merbau District. The greedy algorithm is an algorithm that chooses the best solution at each step, hoping to find the optimal solution as a whole. This research was conducted using data on the location of disaster points, the location of aid distribution points, and the distance between points. The results showed that the greedy algorithm can produce a faster aid distribution route compared to the conventional route.